Constituents of Green Energy Development in Libya and its Challenges (Libya Journal of Geographical Studies, 2023)
Libya is one of the North African countries producing traditional energy based on fossil fuels, and there is no doubt that global crises , have negatively affected oil production. And the opportunity to save energy, and many crises, especially the Covid-19 crisis, which affected the oil market mainly, and the State of Libya suffers from a large deficit in providing energy and covering domestic consumption, especially in the summer, as the production of electricity reached nearly 5000 megawatts, and consumption It reached 8000 megawatts, until mid-2021, and therefore the state, can turn to other renewable sources, to produce electric energy. Fossil fuels, and from what the study concluded, that despite the possibilities available to develop and develop renewable energy projects, they face a large number of challenges, including technical challenges, including financial challenges, in addition to the lack of local security and stability. Then the study came out with a number of recommendations, most notably, issuing Laws and legislation that help local and foreign investment in the field of renewable energies, and work to exploit the silicon available in large quantities in Libyan territory, to make olfactory mirrors and photovoltaic cells, with an emphasis on providing the appropriate budget for the implementation of all planned projects, restarting the stalled projects, in addition to developing the infrastructure necessary to implement renewable energy projects.
Keywords: renewable energy; fossil fuels; solar energy; wind energy; cost; environmental dimensions